Cloning and Inactivation of Genes Encoding Ferredoxin- and NADH-Dependent Glutamate Synthases in the Cyanobacterium Plectonema boryanum. Imbalances in Nitrogen and Carbon Assimilations Caused by Deficiency of the Ferredoxin-Dependent Enzyme - Okuhara, Hiroaki (American Society of Plant Physiologists, 1999)
Glutamate synthase (GOGAT) is a key enzyme in the assimilation of inorganic nitrogen in photosynthetic organisms. We found that, like higher plants, the facultative heterotrophic cyanobacterium Plectonema boryanum had ferredoxin (Fd)- and NADH-dependent GOGATs. The genes glsF, gltB, and gltD were cloned, and structural analyses and target mutageneses demonstrated that glsF encoded Fd-GOGAT and that gltB and gltD encoded the two subunits of NADH-GOGAT. All three mutants lacking one of the GOGAT genes were able to grow photosynthetically and heterotrophically. However, the Fd-GOGAT mutant exhibited a phenotype of marked nitrogen deficiency when grown under conditions of saturating illumination and CO(2) supply. In these conditions the rate of the ammonia uptake from the culture medium was slower in the Fd-GOGAT mutant than in the wild type or in the NADH-GOGAT mutant, but no significant differences were found in the rate of the CO(2) fixation-dependent O(2) evolution among these strains. Our results suggest that, although both Fd- and NADH-GOGATs were operative in the cells growing in light, the contribution of Fd-GOGAT, which directly utilizes photoreducing power for the catalytic reaction, is essential for balancing photosynthetic nitrogen and carbon assimilation.